In situ gelation strategy based on ferrocene-hyaluronic acid organic copolymer biomaterial for exudate management and multi-modal wound healing. (December 2022) - Zhang, Rui; Wang, Sixue; Ma, Xiaofan; Jiang, Shan; Chen, Taoxi; Du, Yuhao; Cheng, Muhua; Liu, Jun; Yuan, Yue; Ye, Tiantian; Wang, Shujun
Abstract: Exudate management remains a major concern in slow or non-healing wound management. Therefore, there is a need to devise a massive exudate-absorbing, exudate-locking, and stable extracellular matrix structure-maintaining functional wound dressing. Inspired by metal-organic frameworks, we chemically introduced sandwich ferrocene (Fc) into hyaluronic acid (HA) to fabricate an innovative metal Fc-HA organic copolymer (FHoC) as the skeleton material for in situ gelation, which was then gently compressed into a pre-hydrogel patch (FHoCP). Fc promoted the rearrangement of polymer chains to form additional microcrystalline and hydrophobic regions, which improved hydrogel transition and the exudate-locking ability. Thus, the simple composition FHoCP(5) absorbed 150 times its weight of water and maintained a firm three-dimensional network, which contributed to reducing inflammation and acted as a physical barrier against hemostasis and anti-bacterial invasion. Meanwhile, multi-modal processes, including fibroblast migration, angiogenesis, and antibacterial effects, were integrated into the gelled FHoCP(5) guided by Fe to promote wound healing. This study suggested that FHoC biomaterial could accelerate the closure of chronic wounds. We believe that this unique FHoCP(5)-based in situ gelation strategy could provide a solid drug-loaded scaffold for cell or adjunctive drug therapies, which holds great potential for the development of multifunctional biomaterials. Statement of significance: Hydrogels that absorb excessive exudates while maintaining stable ECM-like network as well as exert multimodal wound healing activities are ideal dressings for accelerating chronic wound contraction. Herein, we reported an innovative metal ferrocene-hyaluronic acid organic copolymer patch (FHoCP) and FHoCP-mediated in situ gelation strategy. Ferrocene (Fc) induced in situ gelation by promoting polymer chain rearrangement, acting as a physical barrier for hemostasis and anti-bacterial invasion, and absorbing massive exudates, resulting in reducing delayed inflammation. As the structural core, rigid Fc enhanced the stability of the hydrogel backbone, and hydrophobic Fc improved fibroblast migration. In addition, Fe 2+ chemically inhibited bacteria and increased angiogenesis. These results indicated the potential of FHoCP-based hydrogel for application in clinical skin reconstruction. Graphical abstract: Image, graphical abstract